Clinico-Radiographic spectrum of cleidocranial dysplasia: A case series - Nayak, Pooja; Munde, Anita; Deshpande, Anuja; Sawade, Ruchira (Indian Journal of Case Reports, 2020)
Cleidocranial dysplasia (CCD) is a rare autosomal dominant disorder that presents with skeletal dysplasia and dental manifestations. The most common features seen in CCD are aplastic or hypoplastic clavicles, late closure of fontanelles, open skull sutures, and dental abnormalities which include mainly delayed exfoliation of primary teeth and delayed eruption of permanent teeth, with multiple impacted supernumeraries. A relatively low number of multiple case studies are reported in the literature, with only eight reporting on more than three affected individuals. Here, we report a case series of five such rare cases showing characteristic clinical and radiographic features of CCD.